Percutaneous transcatheter embolization in large tortuous coronary artery fistula patient: a case report - Diar Pasahari; Ruth Irana Gunadi; Pandit Bagus Tri Saputra; Makhyan Jibril Al Farabi; Terrence Timothy Evan Lusida; Yudi Her Oktaviono (Journal of the Pakistan Medical Association, 2024)
Coronary artery fistula is a rare anomaly involving the coronary artery and a heart chamber or vessel. Percutaneous intervention has been shown to be effective and safe in fistulas that are small and nontortuous; however, it is not an absolute contraindication in fistulas that are large and tortuous. We report a delayed diagnosis of a single, large-diameter, tortuous coronary artery fistula that manifested as myocardial ischaemia due to the steal phenomenon in a 49 year old male. The undesirable connection was successfully obliterated by percutaneous embolisation, followed by an improvement in symptoms and daily activities. Steal phenomenon is the fundamental mechanism of myocardial ischaemia in coronary artery fistula, as confirmed by improvement in symptoms and coronary artery perfusion following occlusion of the fistula. Percutaneous catheterization is safe and effective for coronary artery fistula closure, and the occlusion site should be precise to achieve complete occlusion and prevent complications. Keywords: Coronary, Fistula, Perfusion, Catheterization, Ischemia,